Six-Year Real-World Outcomes of Antivascular Endothelial Growth Factor Monotherapy and Combination Therapy for Various Subtypes of Polypoidal Choroidal Vasculopathy - Jingyuan Yang; Mingzhen Yuan; Song Xia; Youxin Chen (Journal of Ophthalmology)
The purpose of this study was to compare 6-year visual outcomes of antivascular endothelial growth factor (anti-VEGF) monotherapy and initial combination therapy of photodynamic therapy (PDT) and anti-VEGF therapy for polypoidal choroidal vasculopathy (PCV) in a Chinese population and to investigate imaging biomarkers associated with visual outcomes. Forty-eight treatment-naive PCV eyes of 46 patients were reviewed retrospectively, which underwent anti-VEGF monotherapy or initial combination therapy. PCV was classified into 2 subtypes. Mean best-corrected visual acuity (BCVA) using logarithm of minimal angle resolution and imaging morphological features was compared. No significant differences of mean BCVA changes were noticed between anti-VEGF monotherapy and combination therapy in either subtype 1 PCV or subtype 2 PCV during 6-year period (all P values >0.05). Compared with BCVA at baseline, the mean BCVA at 72 months deteriorated significantly in eyes with subtype 1 PCV (P<0.001), while the mean BCVA at 72 months remained stable in eyes with subtype 2 PCV (P=0.941). In subtype 2 PCV eyes with continuous retina pigment epithelium, the mean changes of BCVA in eyes treated with anti-VEGF monotherapy were better than those in eyes treated with combination therapy (P=0.020). Anti-VEGF monotherapy and combination therapy for various subtypes of PCV had comparable long-term visual outcomes in most cases in real world. Imaging biomarkers which correlate with visual outcomes and treatment response should be included in the classification of PCV and validated in real world.